Ombilin Coal Mine Site: History and Potential as a Learning Source for the History of the Economy Based on Outdoor Learning - Rosmati Rosmiati; Anny Wahyuni; Amir Syarifuddin (BIRCU, 2020)
This study aims to determine the history of the Ombilin Sawahlunto coal mine, the use of this site as a historical learning resource based on outdor learning and the obstacles it faces in its utilization. The method used in this research is qualitative with a descriptive approach. The sources used were interviews, literature and newspapers. After collecting the sources and separating the primary and secondary sources, rewrite them. The research results found that government projects in the city of sawahlunto consist of three projects including first, exploitation of coal mines, second, construction of railways, third, construction of the port of Emmahaven (Teluk Bayur). Traces of Dutch heritage that still exist today are the railway museum, Goedang Ranseum, Mbah Soero Mine Hole, and the Coal Mining Museum. This legacy can be used as a source of historical learning based on outdor learning.